( x+1/x-1 - x-1/x+1 ) ÷ (x-1/x+1 + x+1/x-1) = 2x/x²+1 prove it
Attachments:
![](https://hi-static.z-dn.net/files/de1/d43e3c8664fd71ef03d2596180f3ec26.jpg)
Answers
Answered by
0
Answer:
here answer for your question
Attachments:
![](https://hi-static.z-dn.net/files/dc3/e61c6515d08a63952c8fdf8be7e0f17f.jpg)
Answered by
17
Answer:
Simplified value of this equation is 2x / ( x^2 + 1 ).
Step-by-step explanation:
Using :
- ( a + b )^2 - ( a - b )^2 = a^2 + b^2 + 2ab - ( a^2 + b^2 - 2ab ) = 4ab
- ( a - b )^2 + ( a + b )^2 = a^2 + b^2 - 2ab + a^2 + b^2 + 2ab = 2( a^2 + b^2 )
- ( a + b )( a - b ) = a^2 - b^2
Hence,proved.
Similar questions
English,
6 months ago
Biology,
6 months ago
Social Sciences,
6 months ago
Social Sciences,
1 year ago
Computer Science,
1 year ago